2020
DOI: 10.1016/j.mtnano.2020.100084
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticles in regenerative medicine: what of their fate and impact in stem cells?

Abstract: With advancing developments over the use of magnetic nanoparticles in biomedical engineering, and more specifically cell-based therapies, the question of their fate and impact once internalized within (stem) cells remains crucial. After highlighting the regenerative medicine applications based on magnetic nanoparticles, this review documents their potential cytotoxicity and, more importantly, underscores their valuable features for stem cell differentiation. It then focuses on the transformations magnetic nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 269 publications
(389 reference statements)
1
56
0
Order By: Relevance
“…Iron oxide magnetic nanoparticles (MNPs), such as magnetite (Fe 3 O 4 ) and its oxidized form maghemite (γ-Fe 2 O 3 ), emerged as promising nanotheranostic agents due to their versatile magnetic properties, their biocompatibility, and their biodegradability [1]. Consequently, MNPs have made their way into different applications in the biomedical field including, among others, MRI contrast agents [2], drug delivery [3], tissue engineering [4,5], magnetic targeting [6][7][8][9], and as heat mediators in magnetic hyperthermia (MHT) cancer therapy [10,11]. Unlike other thermal nanotherapies, MHT can be used non-invasively at any depth in tissues, but it still suffers from major restrictions mainly due to the low yield of heat generated per mg. Consequently, several approaches have been suggested to overcome these limitations: among them, one is based on the synthesis of novel nanostructures having an optimized heating [12][13][14]; another consists of the association of MNPs with other heat-generating materials, such as plasmonic ones, specifically designed for photothermal (PT) therapy, resulting in a multifunctional magneto-plasmonic nanohybrid platform.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron oxide magnetic nanoparticles (MNPs), such as magnetite (Fe 3 O 4 ) and its oxidized form maghemite (γ-Fe 2 O 3 ), emerged as promising nanotheranostic agents due to their versatile magnetic properties, their biocompatibility, and their biodegradability [1]. Consequently, MNPs have made their way into different applications in the biomedical field including, among others, MRI contrast agents [2], drug delivery [3], tissue engineering [4,5], magnetic targeting [6][7][8][9], and as heat mediators in magnetic hyperthermia (MHT) cancer therapy [10,11]. Unlike other thermal nanotherapies, MHT can be used non-invasively at any depth in tissues, but it still suffers from major restrictions mainly due to the low yield of heat generated per mg. Consequently, several approaches have been suggested to overcome these limitations: among them, one is based on the synthesis of novel nanostructures having an optimized heating [12][13][14]; another consists of the association of MNPs with other heat-generating materials, such as plasmonic ones, specifically designed for photothermal (PT) therapy, resulting in a multifunctional magneto-plasmonic nanohybrid platform.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we provide a detailed comparative analysis of the thermal potential in both MHT and PT modalities of two differently shaped MNPs, rock-like nanospheres, and multicore magnetic nanoflowers. The rock-like nanospheres obtained by co-precipitation are among the most studied NPs in the field of biomedical applications with high biocompatibility, as, for instance, tested within human mesenchymal stem cells [4,28], while the nanoflowers obtained by the polyols process are among the best known nanoheaters in MHT [29][30][31]. The optical properties of the as-prepared magnetite NPs showed the presence of an intervalence charge transfer band (IVCT) in the NIR-II window, which disappeared in the oxidized maghemite form.…”
Section: Introductionmentioning
confidence: 99%
“…the heart) [ 11 , 12 ], or to be exploited for tissue engineering [ 13 ]. Ahead of these applications, many works have demonstrated that iron oxide nanoparticles can be efficiently taken up for instance by stem cells without affecting their function or their capacity for differentiation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, magnetic particles can influence the phenotype and function of some cells, 19 , 20 in addition to affecting cell viability. 21 , 22 …”
Section: Introductionmentioning
confidence: 99%